ARCHIMEDES OPTIMIZATION ALGORITHM-BASED PITCH ANGLE CONTROL IN WIND ENERGY SYSTEMS - Perçin, Hasan Bektaş; Çalışkan, Abuzer (Bilal GÜMÜŞ, 2024)
Variable-speed wind energy systems equipped with permanent magnet synchronous generators (PMSGs) have become a common configuration in wind energy industry. Appropriate pitch angle control is designed to limit the output power of the system by adjusting the pitch angle of the wind turbine blades at higher wind speeds. This approach reduces mechanical stress on the turbine, extends its operating speed range, and increases the overall lifespan. Intelligent control methods, such as optimization algorithms, are notable for their fast and reliable control performance; however, their use in pitch angle control applications remains relatively limited. In this study, a pitch angle control based on the Archimedes Optimization Algorithm (AOA) was developed and analyzed using MATLAB/Simulink. The proposed control system demonstrated fast and stable performance at higher wind speeds. Additionally, the control mechanism was set to deactivated at lower wind speeds to optimize energy efficiency for varying conditions. When compared to other conventional control methods, alternative approaches generally achieve an average accuracy of %75 to %80. However, the proposed control method performed a significantly faster convergence speed and achieved an accuracy rate exceeding %90.
Keywords: Power Plants; Elektrik Tesisleri; Energy; Enerji; Wind Energy Systems; Rüzgar Enerjisi Sistemleri; Renewable Energy Resources; Yenilenebilir Enerji Sistemleri